Dogme approach in asynchronous discussion to enhance EFL learners’ writing achievement: A quasi-experimental study (Englisia : Journal of Language, Education, and Humanities, 2025)
This study explores the effectiveness of Dogme, a communicative approach, in enhancing the writing skills of English as a Foreign Language (EFL) high school students through asynchronous discussions. By integrating Dogme principles, which prioritize student interests and emergent language, the study aims to improve the efficacy of asynchronous discussions in language learning. A quasi-experimental quantitative design was employed, involving a class of high school students who participated in six asynchronous discussion sessions modified with Dogme principles. Data were collected via pre- and post-intervention writing tests, with student writings evaluated across five aspects. The results, analyzed using a Repeated Measures t-test, revealed significant improvement in writing achievement, evidenced by a higher post-test mean score (82.1) compared to the pre-test (69.8), with a two-tailed significance value below 0.05. This enhancement is attributed to students’ ability to choose discussion topics and utilize emergent language, enabling richer content development in their writing. Thus, this study confirms the viability of incorporating Dogme principles into asynchronous EFL teaching methods to boost writing performance.
Keywords: asynchronous discussion; Dogme approach; writing achievement